Aucubin Impeded Preosteoclast Fusion and Enhanced CD31hi EMCNhi Vessel Angiogenesis in Ovariectomized Mice. (9th November 2022) - Li, Ziyi; Liu, Chang; Liu, Xiaoli; Wang, Na; Gao, Liu; Bao, Xiaoxue; Liu, Sijing; Xue, Peng
Abstract : Osteogenesis is tightly correlated with angiogenesis during the process of bone development, regeneration, and remodeling. In addition to providing nutrients and oxygen for bone tissue, blood vessels around bone tissue also secrete some factors to regulate bone formation. Type H vessels which were regulated by platelet-derived growth factor-BB (PDGF-BB) were confirmed to couple angiogenesis and osteogenesis. Recently, preosteoclasts have been identified as the most important source of PDGF-BB. Therefore, inhibiting osteoclast maturation, improving PDGF-BB secretion, stimulating type H angiogenesis, and subsequently accelerating bone regeneration may be potent treatments for bone loss disease. In the present study, aucubin, an iridoid glycoside extracted from Aucuba japonica and Eucommia ulmoides, was found to inhibit bone loss in ovariectomized mice. We further confirmed that aucubin could inhibit the fusion of tartrate-resistant acid phosphatase (TRAP) + preosteoclasts into mature osteoclasts and indirectly increasing angiogenesis of type H vessel. The underlying mechanism is the aucubin-induced inhibition of MAPK/NF- κ B signaling, which increases the preosteoclast number and subsequently promotes angiogenesis via PDGF-BB. These results prompted that aucubin could be an antiosteoporosis drug candidate, which needs further research.